Analysis of molecular ligand functionalization process in nano-molecular electronic devices containing densely packed nano-particle functionalization shells. (18th June 2022) - Sher, Omer; Han, Yuanyuan; Xu, Haoyuan; Li, Hu; Daun, Tianbo; Kumar, Sharath; Grigoriev, Anton; Panda, Pritam Kumar; Orthaber, Andreas; Serein-Spirau, Francoise; Jarrosson, Thibaut; Jafri, S Hassan M; et al.
Abstract: Molecular electronic devices based on few and single-molecules have the advantage that the electronic signature of the device is directly dependent on the electronic structure of the molecules as well as of the electrode-molecule junction. In this work, we use a two-step approach to synthesise functionalized nanomolecular electronic devices (nanoMoED). In first step we apply an organic solvent-based gold nanoparticle (AuNP) synthesis method to form either a 1-dodecanethiol or a mixed 1-dodecanethiol/ ω -tetraphenyl ether substituted 1-dodecanethiol ligand shell. The functionalization of these AuNPs is tuned in a second step by a ligand functionalization process where biphenyldithiol (BPDT) molecules are introduced as bridging ligands into the shell of the AuNPs. From subsequent structural analysis and electrical measurements, we could observe a successful molecular functionalization in nanoMoED devices as well as we could deduce that differences in electrical properties between two different device types are related to the differences in the molecular functionalization process for the two different AuNPs synthesized in first step. The same devices yielded successful NO2 gas sensing. This opens the pathway for a simplified synthesis/fabrication of molecular electronic devices with application potential.